(untitled) (Journal of actual problems of jurisprudence, 2023)
The article examines the issues of the formation of the theory of evidence and evidence in administrative proceedings. Judicial proving is an activity to clarify the situation in which the judge can draw a conclusion and decide on the case. The evidence of administrative proceedings is all the real data on which the judge determines the presence or absence of administrative offenses, the guilt of this person and other situations important for the correct resolution of the case. Judicial proof is an intersectoral institution inherent in all branches of procedural law. Both the Civil Procedure Code of the Republic of Kazakhstan, the Criminal Procedure Code of the Republic of Kazakhstan, and the Administrative Procedural and Procedural Code of the Republic of Kazakhstan contain a chapter devoted to judicial proof and evidence, which corresponds to the intersectoral nature of this institution. The article analyzes the provisions of administrative proceedings and procedural norms of the Republic of Kazakhstan and formulates proposals for improvement. For the most part, proving in administrative proceedings is subject to the general rules of the Civil Procedure Code of the Republic of Kazakhstan, but there are features provided for in the Administrative Procedural and Procedural Code of the Republic of Kazakhstan. Key words: evidence, evidence, administrative process, court, public law relations; active role of the court; burden of proof.